The Effect of Production and Sales Costs on Net Income in Automotive Subsector Manufacturing Companies and Other Components Listed on The Idx - Suparno Suparno; Gina Maulani Sajili (FEB Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to learn more about Production Costs and Sales of Net Profit in the automotive sub-sector manufacturing companies and other components listed on the Indonesia Stock Exchange. This study was conducted on the auto manufacturing manufacturing sub-sector and other components listed on the Indonesia Stock Exchange in the 2013-2019 period. The sampling technique was purposive sampling, the samples in this study were Production Costs (X1), Sales (X2) and Net Profit (Y). The method used in this study is the verification method using quantitative. Data were analyzed using multiple linear regression analysis and hypothesis testing using t test and f test. The results in this study indicate that the simultaneous Production and Sales Costs to net income, obtained from the value of Fcount 5.590 is greater than Ftable 3.28. The cost of production to net profit obtained from t count 2.141 is greater than t table 2.035. Sales are not partial to net income obtained from t count 1.608 smaller than t table 2.035. Test r2 for Production Costs against Net Income of 17.5%, test r2 for Sales of Net Profit of 12.7%. For the r2 test of Production and Sales Costs to Net Profit of 0.213 obtained from Adjusted R Square, it means that 21.3% of net income is needed by these two variables, while 78.7% of net income is needed by other variables that are not necessary in this study.